Is TSH necessary for initial assessment of thyroid nodules?. (22nd September 2016) - Cai, Haidong; Qiao, Yu; Xi, Hao; Luo, Qiong; Yuan, Xueyu; Yang, Yuehua; Lv, Zhongwei
Summary: Objective: The use of thyrotropin (TSH) in the initial assessment of thyroid nodules is inefficient and leads to unnecessary assessment costs. We compared the total costs of thyroid nodule assessment with or without the use of TSH in the initial assessment. Methods: A total of 1808 patients with thyroid nodules received TSH, fine‐needle aspiration (FNA) and thyroid scintigraphy (TS) assessment, including 83 autonomously functioning thyroid nodule (AFTN) cases and 1725 non‐AFTN cases. The total costs of the TSH strategy and non‐TSH strategies were compared. The ratio of single‐use costs of FNA to TS (CFNA / TS ) was used as the main outcome measure. Results: Only when 6·03 ≤ CFNA / TS ≤ 27·17, the lowest total costs were associated with using the conventional TSH strategy. When CFNA / TS <6·03 or CFNA / TS >27·17, the lowest costs were found with FNA and TS, respectively. Conclusion: From the perspective of cost economics, in iodine‐sufficient areas, we recommend that the decision on the use of TSH for the initial assessment of thyroid nodules should be based on the testing costs of FNA and TS in that medical unit.